2020
DOI: 10.3389/fphy.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

In vivo PET/MRI Imaging of the Chorioallantoic Membrane

Abstract: The Hen's Egg Test Chorioallantoic Membrane (HET-CAM) of fertilized chick eggs represents a unique model for biomedical research. With its steadily increasing use, non-invasive in ovo imaging for longitudinal direct quantification of the biodistribution of compounds or monitoring of surrogate markers has been introduced. The full range of imaging methods has been applied to the HET-CAM model. From the current perspective, Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET) appear promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…Although tumors have been already successfully established on the CAM [4,[20][21][22][23][24][25][26][27][28][29], and PET-imaging studies are available [10,24,25,[30][31][32][33][34][35], systematic analyses of their use to evaluate the biodistribution of radiopharmaceuticals and direct comparisons with the in vivo gold standard are still rare [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although tumors have been already successfully established on the CAM [4,[20][21][22][23][24][25][26][27][28][29], and PET-imaging studies are available [10,24,25,[30][31][32][33][34][35], systematic analyses of their use to evaluate the biodistribution of radiopharmaceuticals and direct comparisons with the in vivo gold standard are still rare [10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the use of radiolabeled compounds and contrast agents for PET and MRI, respectively, have led to the need for suitable models for biodistribution and target specificity studies (Figure 3). The emergence of the CAM and its utility for imaging studies have been extensively reviewed [97]. The CAM offers, in a relatively quick and cost-effective manner, a platform to perform initial evaluations of novel MRI contrast agents and radiolabeled PET tracers.…”
Section: Applications In Imaging and Detectionmentioning
confidence: 99%
“…In certain cases, technologies evaluated on CAM tumor models are specifically developed for tumor imaging. Thus, tumor growth and other features of the embryo are monitored and visualized, for instance using MRI [140,160], MRI/PET [97], and PET/CT [98] (Figure 3).…”
Section: Imaging Of the Tumor And Vascular Networkmentioning
confidence: 99%
“…Based on own previous studies and data from other groups, the model appears suitable for efficient initial in vivo screening of the biodistribution of novel radiolabeled compounds prior to the evaluation in small animals [ 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, testing for target specificity of a radiolabeled tracer by blocking studies has not yet been demonstrated in the CAM model.…”
Section: Introductionmentioning
confidence: 99%